The Science of Social Justice: A Conversation with David Ebershoff. (4th February 2022) - Kemp, Bailey; Severson, Sarah
Abstract: David Ebershoff's biographical novel The Danish Girl focuses on the life of Lili Elbe, one of the first recipients of gender-confirmation surgery. In this interview with Ebershoff, there is discussion about the intertwining roles of art and science both in the novel and in Lili's life, and Ebershoff clarifies how he used Lili's story to create a work of fiction about human agency.